Legislative XML for the semantic web principles, models, standards for document management - Sartor, Giovanni; SpringerLink (Online service). (Dordrecht New York Springer, 2011)
This volume examines the basic layers of the standard-based creation and usage of legislation. In particular, it addresses the identification of legislative documents, their structure, the basic metadata and legislative changes. Since mature technologies and established practices are already in place for these layers, a standard-based approach is a necessary aspect of the up-to-date management of legislative resources. Starting out with an overview of the context for the use of XML standards in legislation, the book next examines the rationale of standard-based management of legislative documents. It goes on to address such issues as naming, the Akoma-Ntoso document model, the contribution of standard-based document management to handling legislative dynamics, meta-standards and interchange standards. The volume concludes with a discussion of semantic resources and a review on systems and projects. - Publisher's description.
Preface; Pompeu Casanovas and Giovanni Sartor.- 1 Introduction: ICT and legislation in the knowledge society; Giovanni Sartor.- 2 Legislative information and the web; Giovanni Sartor.- 3 ICT-based management of legislative documents; Giovanni Sartor.- 4 A standard-based approach for the management of legislative; Fabio Vitali.- 5 Naming Legislative Resources; Enrico Francesconi.- 6 Akoma Ntoso for Legal Documents; Monica Palmirani and Fabio Vitali.- 7 Legislative Change Management with Akoma-Ntoso; Monica Palmirani.- 8 A MetaLex and Metadata Primer: Concepts, Use, and Implementation; Alexander Boer and Tom van Engers.- 9 Semantic Resources for Managing Legislative Information ; Maria Angela Biasiotti.- 10 A Review of Systems and Projects: Management of Legislative Resources; Enrico Francesconi.- Index.
Electronic reproduction.
Keywords: Legislation -- Data processing; Legal documents -- Data processing; Information storage and retrieval systems -- Law; XML (Document markup language).; Semantic Web; Text processing (Computer science).; Electronic books